Posterior reversible encephalopathy syndrome in a patient with underlying mixed connective tissue disease - Das, Malyaban; Mazumdar, Prajit; Kumar, Divakar; Mathur, Vaibhav (International Journal of Research in Medical Sciences, 2018)
Posterior reversible encephalopathy syndrome (PRES) is a condition which is characterized by symmetric involvement of posterior white matter on brain imaging and neurological impairments such as seizures, altered mental status, headache, and visual disturbances. This entity has been classically described with hypertension, renal failure and eclampsia but it can also been seen in cases with normal blood pressure especially in patients receiving immunosuppressive therapy, chemotherapy and in patients with underlying autoimmune disease. Although PRES has been reported with several autoimmune disorders, association of Posterior reversible encephalopathy syndrome (PRES) with mixed connective tissue disease (MCTD) is very rare, hence we report a case of Posterior reversible encephalopathy syndrome in a patient with underlying mixed connective tissue disease (MCTD).